A 112Σ3 grain boundary generated from the decomposition of a Σ9 grain boundary in multicrystalline silicon during directional solidification. (1st July 2019) - Chuang, Lu-Chung; Maeda, Kensaku; Shiga, Keiji; Morito, Haruhiko; Fujiwara, Kozo
Abstract: The generation of a 112Σ3 grain boundary (GB) was observed in situ from the decomposition of a Σ9 GB during directional solidification of multicrystalline Si. A faceted groove formed at the junction of the solid/melt interface and the 112Σ3 GB. This mechanism is different from that for the growth of 111Σ3 GBs, for which no groove formed at the interface. If the growth rates for the adjacent facets of the groove are the same, the GB can grow in a straight manner along the 112 plane. The present results suggest that kinetics can give rise to high-energy GBs during solidification. Graphical abstract: Unlabelled Image